Model Experiment for Mechanical Impact of Karst Cave Location on Metro Tunnel Construction in Urban Shallow-buried Karst Strata - ZHOU Anqi; WANG Shimin; CHEN Fada; WANG Xiang; CHEN Bing (Chengshi guidao jiaotong yanjiu)
[Objective] In the construction of metro tunnels in urban shallow-buried karst environments, it is of great significance to investigate the location of concealed karst caves and their effects on the disturbance of karst strata and the land surface response, which requires thorough analysis and research. [Method] Based on a typical karst tunnel of Guiyang Metro Line 3, a tunnel construction model in karst areas is designed, and a corresponding measurement system is established. Four conditions are selected: no karst cavity (condition 1), karst cavity developed at tunnel vault (condition 2), karst cavity developed at the left arch waist (condition 3), and karst cavity developed at the arch invert (condition 4). 12 excavation steps are designed, and the release of surrounding rock pressure, tunnel arch axial force and bending moment, and land subsidence are analyzed. The monitoring data are converted into engineering prototype results based on similarity ratios. [Result & Conclusion] The presence of concealed karst cavities leads to surrounding rock stress release within a certain range around the cavity. The final release values of surrounding rock pressure for conditions 2, 3, and 4 are 53.8%, 42.0%, and 67.6% of that in condition 1 respectively. The axial force and bending moment of the initial support under condition 3 are 132.9% and 175.6% of those in condition 1, making it the most unfavorable condition. The final land subsidence values at arch vault for conditions 2, 3, and 4 are 32.8 mm, 17.2 mm, and 23.0 mm, respectively, which are 172.6%, 90.5%, and 121.1% of the value in condition 1. The land subsidence amount and range have significantly increased under condition 2.